6x-6+4x=3

Simple and best practice solution for 6x-6+4x=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-6+4x=3 equation:


Simplifying
6x + -6 + 4x = 3

Reorder the terms:
-6 + 6x + 4x = 3

Combine like terms: 6x + 4x = 10x
-6 + 10x = 3

Solving
-6 + 10x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 10x = 3 + 6

Combine like terms: -6 + 6 = 0
0 + 10x = 3 + 6
10x = 3 + 6

Combine like terms: 3 + 6 = 9
10x = 9

Divide each side by '10'.
x = 0.9

Simplifying
x = 0.9

See similar equations:

| 2x-x+5(x+4x)-8-9=20 | | 2x-5x+5(x+4x)-8-9=20 | | 4x*5x=270 | | 17-9+4+6x=19 | | 4x-5(2x+5)=4(x+3) | | 4/3•64 | | 5x-4+-2x+3=-7+-3x+5+2x | | 8x+2x+30=180 | | (2x+y)dx+(x+6y)dy=0 | | -6+4=92 | | -8x+5x+8=10 | | 2q-29=q+16 | | 6-4=92 | | -57+x=63-9x | | y=4/7x=2 | | x+3+x+5= | | b-50=8 | | 2b^2-b-28=0 | | q+23=24q | | 7a+47=25a-25 | | 9b^2-38b+8=0 | | x(0.10)=7194-x | | 4+6(-6-4x)=92 | | 3c=c+44 | | 15.12(x-5)=30 | | 19w-45=4w | | 9y-7=8y | | 3x+5x-2x+18=42 | | x+2(3)=2 | | x(0.06)=6996-x | | 3u-19=2u | | y=(-x^3)+6x |

Equations solver categories